(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the dynamic evolution of English vocabulary in the context of globalization, emphasizing the processes of borrowing, adaptation, and semantic transformation influenced by intercultural communication and technological progress. Globalization, being a multidimensional phenomenon, has accelerated the spread of English as a global lingua franca and contributed to the enrichment of its lexicon with words from diverse linguistic and cultural backgrounds. The study highlights how international trade, migration, digital technologies, mass media, and social networks have served as primary channels for lexical innovation. A particular focus is given to the emergence of new terminologies in science, business, and information technology, as well as the integration of loanwords from Asian, African, and European languages. Furthermore, the research examines the widespread use of abbreviations, acronyms, and neologisms that reflect the fast-paced development of global communication and cultural exchange. In addition to external influences, the article analyzes internal mechanisms of word formation such as compounding, blending, and semantic shift, which enable English to adapt foreign elements into its own system while maintaining linguistic coherence. The role of youth culture, popular media, and online platforms in shaping vocabulary is also addressed, showing how digital globalization fosters creativity and accelerates the diffusion of new lexical items across national boundaries. The study argues that the constant expansion of English vocabulary under globalization not only broadens communicative possibilities but also poses challenges related to linguistic identity, cultural authenticity, and the preservation of native varieties of English. Overall, the article concludes that the globalization-driven evolution of English vocabulary reflects a balance between linguistic innovation and cultural integration. It demonstrates that English continues to be a living, adaptive language, absorbing global experiences and reshaping itself to meet the demands of modern society. The findings are significant for linguists, educators, and translators, as they provide insights into how global processes influence language development and how English serves as both a unifying and diversifying force in the contemporary world.